Incidence, clinical characteristics, and diagnostic approach in transthyretin amyloid cardiomyopathy: The Kumamoto Cardiac Amyloidosis Survey. Issue 1 (July 2022) - Takashio, Seiji; Tokitsu, Takanori; Matsukawa, Masakazu; Sakaino, Naritsugu; Fujimoto, Kazuteru; Sakamoto, Tomohiro; Noda, Katsuo; Tsunoda, Ryusuke; Misumi, Ikuo; Hirai, Nobutaka; Doi, Hideki; Koide, Shunichi; et al.
Highlights: The epidemiology of transthyretin amyloid cardiomyopathy (ATTR-CM) is not yet understood in Japan. We conducted a retrospective multicenter observational cohort study in Kumamoto. The incidence of ATTR-CM was about 1 per 10, 000 person-years in the elderly. Age at diagnosis was older in the regional hospitals than referral facilities. Possible ATTR-CM was more frequent in the regional hospital cohort. Abstract: Background: In recent years, transthyretin amyloid cardiomyopathy (ATTR-CM) has received increasing attention; however, the epidemiology of ATTR-CM in Japan is not yet understood. In the Kumamoto Cardiac Amyloid Survey, we evaluated the current incidence, clinical characteristics, diagnostic approaches, and treatment strategies for ATTR-CM and compared tafamidis-prescription hospitals with regional hospitals. Methods: We conducted a retrospective multicenter observational cohort study. The registry included patients with ATTR-CM diagnosed in two tafamidis-prescription hospital institutes [Japanese Circulation Society (JCS)-certified facilities] and 15 regional cardiovascular facilities in Kumamoto between January 2018 and December 2020. Results: In total, 174 patients were diagnosed with ATTR-CM. The incidence of ATTR-CM was estimated to be approximately 1 per 10, 000 person-years in the elderly population (>65 years old) in Kumamoto. Compared with that in the JCS-certified facilities cohort (n=115), age at diagnosis was significantly older (84.5 ± 5.6 vs. 77.5 ± 6.3 years old; p <0.01) in the regional hospitals cohort (n=59). Histological (25% vs. 81%; p <0.01) and genetic diagnosis (7% vs. 82%) were also less frequently performed. Probable (as indicated by positive bone scintigraphy findings with confirmation of monoclonal protein absence) and possible (as indicated by positive bone scintigraphy findings without confirmation of monoclonal protein absence) ATTR-CM accounted for the majority of cases (75% vs. 19%; p <0.01) in the regional hospitals cohort compared to the JCS-certified facilities cohort. There were no cases of hereditary ATTR-CM among the patients who underwent TTR genetic testing (n=98). Conclusions: We confirmed the incidence of ATTR-CM in Kumamoto and the diagnostic approach used in patients with ATTR-CM. Further prospective studies with a larger sample are needed to validate our results and to further shed light on the epidemiology of ATTR-CM in Japan. Abstract : Image, graphical abstract